Digital Politics of Prabowo: Political Power Representation and Public Engagement on Instagram - Eefendi, Rachmat; Suhartono, Suhartono; Fidiyanti, Murni; Arifin, Samsul (The Sunan Ampel Review of Political and Social Sciences, 2025)
This study explores how President Prabowo Subianto’s official Instagram account is utilized as a strategic tool in digital politics and political communication. By applying a cyber sociopragmatic approach, which integrates sociopragmatic theory (Haugh, Kádár, & Terkouraf) with concepts of digital politics, this research investigates how language, imagery, and symbols are carefully crafted to communicate political authority, represent national identity, and engage with the public. Employing qualitative methods such as observation and document analysis, the study examines how Instagram posts contribute to shaping political narratives and diplomatic discourse, focusing on the symbolic use of protocol, international cooperation, and Indonesia’s foreign relations. The analysis, guided by the social, interactional, and normative dimensions of sociopragmatics, highlights how textual and visual elements work together to convey subtle messages of political power, shape diplomatic relations, and influence public perception. The findings indicate that Instagram is not merely a platform for information sharing, but a political space for constructing political identity, enhancing public engagement, and projecting Indonesia’s presence on the global stage. This research contributes to theoretical development by linking cyber sociopragmatics with digital politics, shedding light on how sociocultural norms and contextual reasoning inform online political communication. Practically, it offers insights into how social media can be strategically leveraged by political leaders to facilitate communication, strengthen domestic and international ties, and navigate the complex landscape of digital political discourse.